COMMUNITY IMPACT FOR CLINICALLY INTEGRATED ATC PROGRAM IN A SPORTSMEDICINE PRACTICE. Issue 7 (30th July 2021) - Grambo, Laura; Rivero, Samantha; Harbacheck, Katie; Boyd, Christine; Keefer, Shaun; Klein, Eric; Vuong, Brian; Ford-Hemann, Carolyn; Larson, Scott; D'Alpe, Cameron; Frick, Steve; Shea, Kevin
Background: Health Systems routinely make investments in clinically driven outreach programs to build for future community needs, improve health outcomes, and serve their community mission. Many community sports programs have limited access to sports medicine care, including access to athletic trainers. Hypothesis/Purpose: The primary purpose of this study was to evaluate the impact of a clinically integrated Certified Athletic Trainer (ATC) Community Sports Outreach Program, by evaluating the outreach into the community, sports clubs, schools, covered events. Methods: The ATC Community Outreach Program monitored key metrics over a 3 and 1/2-year period. Metrics included the partnerships developed with local clubs and schools, number of athletes covered in each organization, games covered and hours spent supporting organizations. Categories were divided into fiscal years (FY) running from September to August. Fiscal Year 2016 was calculated from January – August, as it was the first year of the program. The percentage of growth of the amount of games covered was calculated from the adjacent FY. Results: Over the first 3 and 1/2 years (FY2016-FY2019), the number clubs, schools, programs covered grew from 10, 19, 25, to 31 from FY2016 - FY2019. Number of athletes from 7, 363, 12, 552, 15, 104, to 19, 794 from FY2016 - FY2019. The number of community outreach events grew from 6, 11, 57, to 190 from FY2016 - FY2019 (Table/Figure 1.1). The percentage of growth of games covered grew from 183%, 518% to 333% between FY2016 and FY2019. Discussion/Conclusion: Building, maintaining a sports medicine practice is a complex undertaking, and represents a significant investment for the health system and community. In many communities, access to sports medicine care for athletes is very limited. A clinically integrated ATC program can generate a significant impact on the community by building relationships with local sports clubs/schools and improving sports medicine care access to young athletes. Tables/Figures: Figure 1.1.